The effects of water depth and salt concentration on solar still performance - Lepiten, Isagani Disierto (1971)
The possible effects of water depth and concentration on solar still performance was studied by the use of a solar field still. The study was carried out in two parts. First, the water depth was changed from one inch to six inches while the concentration was kept at zero. Second, the concentration was varied from 2.074 to 9.58 percent by weight. The water depth was fixed at two inches.The results indicate that productivity was increased by 70 percent over that of the 1-inch depth yield. This confirms the work of Bloemer, et. al. (5). The effect of concentration is in agreement with the theoretical computation based on Raoult's law. It is shown that the effect of concentration is nil.
Thesis (M.S. Mechanical Engineering)--University of the Philippines.
Keywords: Sea-water, Distillation of